Bacillus velezensis promotes the proliferation of lactic acid bacteria and influences the fermentation quality of whole-plant corn silage - Wang, Yili; Ying, Gangqing; Zhang, Zimo; Tang, Yu; Zhang, Yunhua; Chen, Lijuan (Frontiers in Plant Science, 2024)
This study aimed to investigate the promoting effect of a Bacillus velezensis (BV) strain on lactic acid bacteria (LAB) and determine its influence on the fermentation quality and aerobic stability of silage. Flat colony counting method was used to evaluate the effect of BV on the growth of LAB. The results indicated that BV exhibited a proliferative effect on Weissella confusa, Lactobacillus plantarum L-2, and Pediococcus pentosaceus. Freshly harvested whole-plant corn was inoculated separately with BV and L. plantarum (LP), along with an uninoculated control group (CK), and assessed at 1, 3, 5, 7, 15, and 30 days of ensiling. Results exhibited a more rapid pH reduction in BV-inoculated silage compared with that in CK and LP-inoculated silage during the initial stage of ensiling. Throughout ensiling, the BV and LP experimental groups showed enhanced silage fermentation quality over CK. Additionally, relative to LP-inoculated silage, BV-inoculated silage displayed reduced pH and propionic acid. BV also prolonged aerobic stability under aerobic conditions. The microbial community in BV-inoculated silage showed greater stability than that in LP-inoculated silage. Additionally, Firmicutes and Lactobacillus exhibited more rapid elevation initially in BV versus LP-inoculated silage, but reached comparable levels between the two inoculation groups in the later stage. In summary, BV enhanced the efficacy and aerobic stability of whole-plant corn silage fermentation by stimulating LAB proliferation.